Management of complex weed flora of wheat (Triticum aestivum) through appropriate herbicides - SINGH, R K; TRIPATHI, U K; SINGH, S R K (The Indian Journal of Agricultural Sciences, 2022)
Field experiment was conducted at the Instructional Farm of Krishi Vigyan Kendra, Chhatarpur during rabi 2017–18 and 2018–19 to evaluate appropriate herbicides for effective management of complex weed flora of wheat crop. The present investigation concluded that the use of single herbicide was either ineffective or less effective against complex weed flora. However, combination of two or more compatible herbicide molecules like clodinafop propargyl + metsulfuron-methyl and sulfosulfuron + metsulfuron-methyl was quite effective against complex weed flora in wheat resulting in higher WCE, WCEI, yield and economic net return/unit area (85.9% broad leaved weeds and 90.3% narrow leaved weeds, 87.2%. 39.9 q/ha and `46103/ha), respectively, followed by application of Sufosulfuron + metsulfuron methyl (82.4% broad leaved weeds and 85% narrow leaved weeds, 81.1%, 38.8 q/ha and `43936/ha), respectively, as compared to control plot. Therefore, the combination of two compatible herbicide molecules clodinafop propargyl + metsulfuron-methyl and sulfosulfuron + metsulfuron-methyl is quite effective against complex weed flora in wheat. This can be a better alternative for managing complex weed flora in the wheat field than the sole herbicide.